(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Forty two hybrids generated by crossing three testers with fourteen lines were studied along with parents for studying heterosis and gene action for days to first flowering, days to 50 percent flowering, fruit weight, fruit length, plant height, number of seeds per fruit, 100-seed weight and fruit yield per plant during rainy season and summer season of 2002-03 at Department of Horticulture, Indira Gandhi Agricultural University, Raipur, Chhattisgarh, India. The most heterotic combinations were VRO-6 x Parbhani Kranti, VRO-4 x Parbhani Kranti, Daftari-1 x Arka Abhaya and Kaveri Selection x Ankur Abhaya for fruit yield per ptant. The sca variances for days to fruit flower, days to 50 percent flowering, fruit weight, fruit length, plant height, number of seeds per fruit and 100-seed weight were higher than so gca variance so there is a preponderance of non-additive gene action. The gca variances was greater than sca variances for fruit yield per plant indicating preponderance of additive gene action for this trait. Overall, the results discussed above are quite indicative of the fact that hybrid okra has great potentialities of maximizing fruit yield in Chhattisgarh plains. DOI: http://dx.doi.org/10.3329/bjar.v32i3.544 Bangladesh J. Agril. Res. 32(3) : 421-432, September 2007